2020
DOI: 10.3390/plants9111412
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Seed Weight, Amino Acid, Fatty Acid, Oil, and Squalene Content in γ-Irradiation-Developed and Commercial Amaranth Varieties (Amaranthus spp.)

Abstract: Grain amaranth is known as an alternative crop with exclusive nutritional value and health benefits. The purpose of this study was to investigate the effect of gamma irradiation on quantitative and qualitative amaranth seed traits, including 1000-seed weight, amino acids, fatty acids content, oil, and squalene yield. Two Slovak mutant varieties “Pribina” (A. cruentus) and “Zobor” (A.hypochondriacus x A. hybridus) were evaluated and compared to nonirradiated controls Ficha (A. cruentus L.) and K-433 (A. hypocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…Pospišil et al [46] reported an average 1000-seed weight of 0.65-0.73 g for two amaranth species, which was significantly increased by nitrogen fertilization in the dry season. Compared to the commercial grain varieties Plainsman (0.71 g) and Koniz (0.69 g), the hybrid variety 'Zobor' showed 1000-seed weight up to 18% and 21% higher, respectively [23].…”
Section: Evaluation Of Phenotypic Traits and Weight Of 1000 Seedsmentioning
confidence: 85%
See 2 more Smart Citations
“…Pospišil et al [46] reported an average 1000-seed weight of 0.65-0.73 g for two amaranth species, which was significantly increased by nitrogen fertilization in the dry season. Compared to the commercial grain varieties Plainsman (0.71 g) and Koniz (0.69 g), the hybrid variety 'Zobor' showed 1000-seed weight up to 18% and 21% higher, respectively [23].…”
Section: Evaluation Of Phenotypic Traits and Weight Of 1000 Seedsmentioning
confidence: 85%
“…The increased seed size and yield could have a negative impact on the nutritional properties of amaranth seeds [47]. However, our previous studies [22,23,48] showed high nutritional quality of the amaranth germplasm obtained by γ-radiation with higher seed weight.…”
Section: Evaluation Of Phenotypic Traits and Weight Of 1000 Seedsmentioning
confidence: 93%
See 1 more Smart Citation
“…The weights obtained in this study (based on 100 seeds per sample) were similar to those reported by De Bock et al in 2021 [ 19 ]. Other authors have reported highly variable values, ranging from 0.03 to 0.79 g, including species such as Amaranthus hypochondriacus [ 20 , 21 , 22 ]. However, in the present study, 6–32% higher seed weight was noted for MX1 and PU compared to the other three samples, which is consistent with their larger seed sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The FAME profile was analyzed by gas chromatography (GC-6890-N, Agilent Technologies, Santa Clara, USA) equipped with capillary column DB-23 (60 m × 0.25 mm, film thickness 0.25 µm, Agilent Technologies, Santa Clara, CA, USA) and FID detector (250 °C; constant flow, hydrogen 40 mL/ min, air 450 mL/min.). A detailed description of the chromatography conditions is presented in the work Szabóová et al (2020). Standards of a C4-C24 FAME mixture (Supelco, Bellefonte, PA, USA) were applied in order to identify FAME peaks.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%